The Utilization Rubber Wood Finger Joint Laminated for Furniture Application - Nurhanifah; Wijayanto, Arip; Anggiriani, Siska; Muhamad, Soleh; Mulyosari, Desy (Journal of Sylva Indonesiana, 2025)
Rubber wood (Hevea brasiliensis) was considered a promising alternative material in furniture manufacturing due to its favorable physical and mechanical properties, sufficient availability, and relatively high economic value. However, it lacked natural durability and was vulnerable to insect and fungal attacks, requiring preservative treatment before use. This study aimed to evaluate the performance of Finger Joint Laminated (FJL) products made from preservative-treated rubber wood as a potential raw material for furniture. The research involved wood selection, preservative treatment using deltamethrin and boric acid via the vacuum-pressure method, fabrication of FJL using three adhesive compositions (PVAc, PVAc + 5% hardener, and PVAc + 15% hardener), and testing of physical (moisture content and density) and mechanical (modulus of elasticity and modulus of rupture) properties according to BS 373:1957 standards. The results showed that all FJL variants met the density requirements stated in SNI 01-0608-2017. The FJL bonded with 15% PVAc and hardener achieved the highest density and exhibited superior mechanical strength. Although the addition of hardener increased the moisture content, it remained within the acceptable limit (<15%) as defined in SNI 01-0608-1989. The improvement in mechanical performance was attributed to enhanced cross-linking in the adhesive. Some mechanical failures were likely caused by uneven adhesive application. In conclusion, rubber wood treated with preservatives and processed into FJL with optimal adhesive composition demonstrated strong potential as material for furniture production